PECULIARITIES OF THE ULTRABASIC MINERALOGY - CRITERION OF PALEOGEODYNAMIC CONDITIONS OF OPHIOLITE FORMATION IN THE ALTAI-SAYAN FOLDED AREA - Stupakov S.I.; Simonov V.A. (My University, 1997)
New data are reported on the composition of ophiolite ultrabasite minerals from the Altai-Sayan folded area (ophiolite associations from the Altai Mountains, Kuznetsk Alatau, West Sayan, and South Tuva). Peculiarities of the mineral compositions show that ultrabasic rocks are represented by two types - mantle tectonites and cumulates. Comparative analysis of studied utrabasite mineralogy and rocks of modern objects permit us to clear up paleogeodynamic environments under which ophiolites were formed. These environments appeared to be similar to the settings in the Western Pacific Ocean.